Development of a mobile application for georeferenced data collection in the field - Silva, Catarina Isabel Rodrigues Pereira da (2020)
Tese de mestrado, Bioinformática e Biologia Computacional, Universidade de Lisboa, Faculdade de Ciências, 2019